Wykorzystanie środowiska przyrodniczego czynnikiem rozwoju regionalnego - Kruk, Hanna (Natural Environment Use as a Factor of Regional Development, 2006)
Natural environment is one of the regional development's factors. Environment can determine on region's attractiveness and competitiveness. In the article a possibility of environment use was presented on the ground of the Vistula Lagoon's region. Described region has significant environmental value, but its potential is not used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 716-723